2018
DOI: 10.3390/min8090384
|View full text |Cite
|
Sign up to set email alerts
|

Rock Classification Using Multivariate Analysis of Measurement While Drilling Data: Towards a Better Sampling Strategy

Abstract: Measurement while drilling (MWD) data are gathered during drilling operations and can provide information about the strength of the rock penetrated by the boreholes. In this paper MWD data from a marble open-pit operation in northern Norway are studied. The rock types are represented by discrete classes, and the data is then modeled by a hidden Markov model (HMM). Results of using different MWD data variables are studied and presented. These results are compared and co-interpreted with optical televiewer (OTV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In theory, various methods, including analytical, numerical, and experimental, can be used to analyze the applicability of MWD to the characterization of coalmine roofs [2][3][4][5][6][7][8]11,[15][16][17]. Analytical and numerical methods provide a straightforward means to understand the immediate effect of various geotechnical parameters on drilling and bolting operations.…”
Section: Methodsmentioning
confidence: 99%
“…In theory, various methods, including analytical, numerical, and experimental, can be used to analyze the applicability of MWD to the characterization of coalmine roofs [2][3][4][5][6][7][8]11,[15][16][17]. Analytical and numerical methods provide a straightforward means to understand the immediate effect of various geotechnical parameters on drilling and bolting operations.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade established methods have been created, such as understanding rock hardness and rock mass through rate of penetration (ROP) and torque [77]. Techniques are starting to differentiate lithologies using petrophysics and fuzzy interference systems by applying multivariate analysis, neuro-adaptive learning algorithms, and/or machine learning [78][79][80]. MWD real-time data can be processed and provide an approximation of rock strength whilst physically drilling [81].…”
Section: Down-the-hole Predictionmentioning
confidence: 99%
“…To overcome the difficulties associated with the uncertainty of geological data, the methods of artificial intelligence, machine learning [17,18], neural networks [12,13,19,20], fuzzy logic [21][22][23], etc., are gaining widespread use in the mining industry. Today there are numerous variations in the indicated methods and tools, which offer cutting-edge solutions to the problems of the mining industry in the presence of input data of different complexity [16,24].…”
Section: Introductionmentioning
confidence: 99%
“…The indicated methods are widely used for the analysis of geomechanical parameters [22], prediction of geological conditions of the rock mass [22,25], calculation of physical and mechanical parameters of the rocks [21], their classification, estimation and prediction of drilling and blasting parameters and indicators [12,13,[18][19][20][21], etc. A detailed review of computing technology applications and the indicated methods in mining is presented in the paper [10].…”
Section: Introductionmentioning
confidence: 99%